Fishery Resources, Ecological Environment Carrying Capacity Evaluation and Coupling Coordination Analysis: The Case of the Dachen Islands, East China Sea - Huang, Hong; Wang, Zuanyi; Li, Yingdong; Zhao, Xu; Wang, Zhenhua; Cheng, Xiaopeng (Frontiers in Marine Science, 2022)
Impacts of human activity on the sustainable development of marine fisheries have been greatly concerned, and carrying capacity with theoretic and practical meanings, has become a focused area over the past two decades. More importantly, there are few studies on the fishery resources and environment compound system. In this study, based on the investigation data in Dachen Islands during 2019–2021, we proposed the evaluation method of fishery resources, ecological environment carrying capacity (FRCC & MEECC), and analyzed the coupling coordination degree between the fishery resources and environment. The results showed that: (1) the MEECC of Dachen Islands was in the critical overload state, fluctuated significantly among seasons, and the winter voyage of 2021 was the worst. (2) The nekton index of Dachen Islands was basically stable, the fish eggs and juvenile index dropped markedly, and the FRCC was also critically overloaded. (3) The fishery resources and marine environment were moderately balanced. Further, the development was relatively synchronized in autumn of 2019 and 2020, while the fishery resources in spring of 2021 lagged behind the marine environment.